2021
DOI: 10.1038/s41419-021-04144-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PCBP1-AS1-mediated AR/AR-V7 deubiquitination enhances prostate cancer enzalutamide resistance

Abstract: The refractory of castration-resistant prostate cancer (CRPC) is mainly reflected in drug resistance. The current research on the resistance mechanism of CRPC is still in its infancy. In this study, we revealed for the first time the key role of LncRNA PCBP1-AS1 in CRPC drug resistance. Through detailed in vivo and in vitro studies, we found that PCBP1-AS1 may enhance the deubiquitination of AR/AR-V7 by stabilizing the USP22-AR/AR-V7 complex, thereby preventing AR/AR-V7 from being degraded through the ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Due to clinical importance and association with biological processes in many malignancies, LINC01116 could be a crucial biomarker for the prediction and therapeutic interventions of malignant tumors ( 64 ). PCBP1-AS1 could facilitate the AR/AR-V7 deubiquitination, resulting in the protection of AR/AR-V7 against degeneration ( 65 ). In vitro and in vivo studies have shown that targeting PCBP1-AS1 may improve the therapeutic responsiveness of enzalutamide-resistant cancers and suppress the metastasis of LUAD ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to clinical importance and association with biological processes in many malignancies, LINC01116 could be a crucial biomarker for the prediction and therapeutic interventions of malignant tumors ( 64 ). PCBP1-AS1 could facilitate the AR/AR-V7 deubiquitination, resulting in the protection of AR/AR-V7 against degeneration ( 65 ). In vitro and in vivo studies have shown that targeting PCBP1-AS1 may improve the therapeutic responsiveness of enzalutamide-resistant cancers and suppress the metastasis of LUAD ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCBP1-AS1 could facilitate the AR/AR-V7 deubiquitination, resulting in the protection of AR/AR-V7 against degeneration ( 65 ). In vitro and in vivo studies have shown that targeting PCBP1-AS1 may improve the therapeutic responsiveness of enzalutamide-resistant cancers and suppress the metastasis of LUAD ( 65 , 66 ). SNHG10 was shown to be overexpressed in gastric cancer (GC) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of PCBP1-AS1 have been studied in multiple tumors. Zhang et al found that higher expressions of PCBP1-AS1 might reveal poorer prognoses for sufferers and might reinforce the deubiquitination of AR/AR-V7 via stabilising the USP22-AR/AR-V7 complexes, hence avoiding AR/AR-V7 degradation via the ubiquitin-proteasome channel [ 33 ]. Luo and his group revealed that PCBP1-AS1 was highly expressed in human hepatocellular carcinoma and markedly related to unsatisfactory prognoses in sufferers with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that LncRNA LINC00675 and HOTAIR were markedly upregulated in androgen-insensitive PCa cell lines and CRPC patients, blocking the interaction of AR proteins with MDM2 and thereby preventing AR ubiquitination and protein degradation ( Zhang et al, 2015 ; Yao et al, 2020 ). LncRNA PCBP1-AS1 ( Zhang B et al, 2021 ) was reported to be able to stabilize AR via promoting the stability of USP22-AR complex by binding to AR NTD domain and enhancing AR de-ubiquitination. Importantly, targeting LINC00675, HOTAIR and PCBP1-AS1 all could effectively inhibit the growth and invasion ability of PCa cells and restore the drug sensitivity of Enzalutamide-resistant PCa cells, which offered distinct view for future clinical utilization.…”
Section: Ar Pathwaymentioning
confidence: 99%